Devellopement motivational attitudes of teachers to integrate ITC (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2014)
This article examines the evolution of motivational attitudes of university teachers vis-vis the integration of information technology and communication (ICT). Motivational attitudes of teachers could be enhanced by the skill. The latter is considered a variable motivation. In this perspective, the technological means that are targeted and used by teachers support the use of active learning. They are at the service of student learning. Thus, the technology is seen as a means to active pedagogies and not as an end in itself. Different motivational variables associated with the integration of ICT are analyzed in this work. Our results show that the use of ICT depends on sense of competence, attractiveness and perceived value of ICT, while the generational difference and gender are not significant.The objective is to strengthen the motivational attitudes of the integration of ICT in teaching and developing technopedagogies